2018
DOI: 10.1039/c8cy00631h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of high-Si hierarchical beta zeolites without mesoporogen and their catalytic application in the methanol to propene reaction

Abstract: High-Si single-crystalline beta zeolites with intracrystal mesopores were synthesized for the first time and investigated as catalysts for the methanol to propene (MTP) reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…12 C/ 13 C‐methanol switch experiments revealed that the olefin methylation/cracking mechanism dominated the reaction. Afterward, hierarchical porous structure was further introduced into high‐silica Beta by using a concentrated system . The low water dosage was found to accelerate the nucleation and crystal growth rate, and promote the formation of nanoaggregates by preventing the further fusion of the primary grains.…”
Section: Toward Enhanced Ethylene or Propylene Selectivitymentioning
confidence: 99%
“…12 C/ 13 C‐methanol switch experiments revealed that the olefin methylation/cracking mechanism dominated the reaction. Afterward, hierarchical porous structure was further introduced into high‐silica Beta by using a concentrated system . The low water dosage was found to accelerate the nucleation and crystal growth rate, and promote the formation of nanoaggregates by preventing the further fusion of the primary grains.…”
Section: Toward Enhanced Ethylene or Propylene Selectivitymentioning
confidence: 99%
“…[369] Bottom-Up Methods-Template-Free: In contrast to previous template-assisted hydrothermal synthesis procedures, two studies have been found that manage to synthesize hierarchical beta zeolites without using any templates. [370,371] Considering the first, Zhao et al executed the crystallization of high Si hierarchical beta zeolites by kinetic regulation of the crystallization process. They worked under low water conditions, which facilitated nucleation and crystal growth and ensured that the fusion of individual nanocrystallites inside the particle is restrained.…”
Section: Betamentioning
confidence: 99%
“…This could be explained by a slower coking rate, which was a consequence of the improved utilization of the interior acid sites, and the enhanced molecular diffusion. [370] Nanozeolites and Their Assembly: Nanostructured beta zeolites can be synthesized in multiple ways. A first method was proposed by Xiong et al who performed an aerosol-assisted hydrothermal method in NaF medium in presence of TEAOH.…”
Section: Betamentioning
confidence: 99%
See 2 more Smart Citations